La sabana arbolada "El Escobio", Liberia, Guanacaste, Costa Rica - Elizondo Castillo, Luis H.; Jiménez Madrigal, Quírico (Revista de Biología Tropical, 1988)
An ecological study of a tree savanna was conducted at “El Escobio”, Liberia, Guanacaste, Costa Rica. The site shows a seasonal climate; with well defined dry and wet seasons. Soils are poor on nutrients, favouring a dominant coverage of herbaceous plants (Cyperaceae and Graminae) more or less xeromorphic, and the growth of some scattered tree species. A great number of rare and economically important species were found at the riparian forest. This forest plays a significative role in keeping a diverse fauna, due to the variety of fruits and flowers available throughout the year.